Energy aware stable path ad hoc on-demand distance vector algorithm for extending network lifetime of mobile ad hoc networks - Tibebu Legesse; Dagne Walle Girmaw; Esubalew Yitayal; Engida Admassu (PLoS ONE, 2025)
Traditional routing protocols in MANETs, such as AODV, do not take energy consumption into account, which leads to inefficient utilization of the limited battery resources. In such networks, nodes depend on non-rechargeable batteries, and once the energy is depleted, the nodes can no longer function, resulting in frequent link failures and reduced network lifetime. To address these challenges, this paper proposed a novel routing protocol, the Energy Aware Stable Path Ad Hoc On-Demand Distance Vector (EASP-AODV), which incorporates residual energy of individual nodes and received signal strength to improve routing decisions. By considering these factors, EASP-AODV effectively reduces link breakages, enhances route stability, and prolongs the overall lifetime of the network. The algorithm optimizes energy usage, ensuring that nodes with higher residual energy are preferred for routing, thus minimizing energy depletion and mitigating early node failures. To evaluate the effectiveness of EASP-AODV, we conducted simulations using NS2.35, a widely used network simulator. The performance of EASP-AODV was compared with two well-known routing protocols: Energy Aware Path Selection (EAPS-AODV) and the traditional AODV. Several performance metrics, including normalized energy consumption, packet delivery ratio, normalized routing overhead, average end-to-end delay, and network lifetime, were measured. Simulation results demonstrate that EASP-AODV outperforms EAPS-AODV and AODV in terms of energy efficiency, with a 4.5% and 9.5% reduction in normalized energy consumption, respectively. Moreover, the proposed algorithm significantly extends network lifetime, with a 3.5% and 7.5% improvement over EAPS-AODV and AODV. These results confirm that EASP-AODV provides a more energy-efficient and sustainable solution for routing in MANETs, addressing the critical issues of energy consumption and network stability while extending the operational lifetime of the network.